Building Competitive Strategies and Managing Stakeholder Relations - Adiguzel, Zafer (Springer International Publishing Ag, 2017)
Stakeholder management and competitive strategy concepts are very important for a company's position and its corporate structure and for understanding which sectors or customer groups have an effect on business, how the company can be successful, and whether the company can respond to the demands and needs of stakeholders. In the traditional view, stakeholders include employees, shareholders, suppliers, and customers; however, the society, nongovernmental organizations, governments, and media also have a significant impact on business. Therefore, stakeholders have been examined as internal and external ones. To achieve sustainability for their business, companies should strategically analyze and evaluate the stakeholders, who are at the core of their activities and fulfill their necessary responsibilities. This study illustrates the performance results of the stakeholder management theory analyses and competitive strategy on globalization: (1) the stakeholders and competitive strategy of the companies suitable for their employees and management team's expectations; (2) determining how to meet the expectations of stakeholders; (3) relations between stakeholders and business performance; and (4) finally, relationships with stakeholders, the strategies for managing stakeholders, and the relationship between the business performance and stakeholders.
Keywords: Capabilities; Management